Percepciones estudiantiles sobre el proceso de acreditación por alta calidad del programa de administración de empresas de la universidad del magdalena - Javier Viloria-Escobar; María Bertel-Narváez; Alexander Daza-Corredor (Universidad del Magdalena, 2015)
This article aimed to explore the perceptions of students of Business Administration Program of the University of Magdalena on the accreditation process for high quality that is submitted to the Ministry of Education. For which a random sample of 100 students was taken, who are part of various academic semesters, answered a questionnaire that asked for their views on the process. The main results support the view that students have a huge sense of belonging to the program and believe that it deserves accreditation by the Ministry and, further, this certificate becomes something positive for their careers. We conclude that, despite the apparent acceptance of the conditions of program quality, it is necessary that efforts be brought forward to create a culture of quality throughout the student population and a and a nationwide study is proposed to investigate these perceptions in various universities in Colombia, having as reference the implications of the context to which they belong.